2010
DOI: 10.4028/www.scientific.net/amm.24-25.413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Drop Weight Impact Performance of Sandwich Panels with Aluminium Honeycomb and Titanium Alloy Micro Lattice Cores

Abstract: Abstract. This paper is a study of the drop weight impact behaviour of small sandwich panels of carbon epoxy skins with aluminium honeycomb and titanium alloy micro-lattice cores. A series of experimental tests have shown that the specific impactor penetration behaviours are similar for both cores. The reasons for this are a result of the detailed deformation and rupture behaviour of the two types of core. The deformation and rupture mechanisms of honeycomb and micro-lattice structures will be discussed in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Another favorite material for SLM is alloyed titanium. Lattice structures of titanium alloys were investigated in [22][23][24]. An interesting combination of materials was investigated in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another favorite material for SLM is alloyed titanium. Lattice structures of titanium alloys were investigated in [22][23][24]. An interesting combination of materials was investigated in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on SLM Ti6Al4V micro-lattice structure as core material in sandwich construction showed that this material has significant potential that merits further examination and analysis [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the Ti‐6Al‐4V powder is more reactive compared to SS316L, and hence is more difficult to work with and gives more variable quality in the final Micro‐lattice structure. A specific application, discussed in ref ,. was that of core material in aerospace sandwich construction, with the specific application of foreign object impact.…”
Section: Micro‐lattice Materials For Ultra‐lightweight Structuresmentioning
confidence: 99%